1979
DOI: 10.1172/jci109312
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to the Phosphaturic and Calcemic Actions of Parathyroid Hormone during Phosphate Depletion

Abstract: A B S T R A C T Recent observations indicate that in thyroparathyroidectomized (TPTX) rats fed a low (0.2 gll00 g) phosphorus diet, the tubular phosphaturic response to parathyroid hormone (PTH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…A decrease in the PTH phosphaturic capacity may be considered to be an associated factor, as described in previous works . A decrease in Pi intake may be also considered because it is known that Pi deprivation produces PTH resistance without altering the cAMP excretion (Gloor et al 1979). We have reported a diminution in the excretion of cAMP in the urine of Altreated rats .…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the PTH phosphaturic capacity may be considered to be an associated factor, as described in previous works . A decrease in Pi intake may be also considered because it is known that Pi deprivation produces PTH resistance without altering the cAMP excretion (Gloor et al 1979). We have reported a diminution in the excretion of cAMP in the urine of Altreated rats .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our preliminary findings lead us first to propose that the physiologic role of FGF23 is to act as a counterregulatory hormone for 1,25(OH) 2 effect would be to increase renal phosphate clearance under circumstances in which phosphate was not needed for mineralization of extracellular matrix. Second, 1,25(OH) 2 D 3 stimulation of FGF23 production by osteoblasts in bone provides a mechanism to maintain phosphate homeostasis in the setting of suppressed PTH secretion (41). In the presence of 1,25(OH) 2 D 3 stimulation of calcium and phosphate absorption by the gastrointestinal tract (42), increments in calcium (as well as 1, 25[OH] 2 D 3 itself) act on the parathyroid gland to suppress PTH, thereby limiting the ability of the kidney to excrete the increased phosphate absorbed from the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that phosphate depletion is associated with hypercalciuria (25,26) and with resistance to the actions of PTH to stimulate tubular reabsorption of calcium (25), to inhibit tubular reabsorption of phosphate (27), and to raise serum calcium (28). The hypercalciuria in phosphate depletion has been attributed to the increase in the filtered load of calcium, which is due to accompanying hypercalcemia, and to the decrease in the tubular reabsorption, which is due to functional hypoparathyroidism (25,29).…”
Section: And 2)mentioning
confidence: 99%